On the dynamic mechanisms of intense rainfall events in the central Andes of Peru, Mantaro valley - Luis Flores-Rojas, Jose (2021)
Present study comes under the project MAGNET-IGP: Strengthening the research line in physics and microphysics of the atmosphere (Agreement No 010-2017-FONDECYT) This work was done using instruments of the Laboratory of Physics, Microphysics and Radiation (LAMAR) and computational resources, HPC-Linux -Cluster, from Laboratorio de Dinamica de Fluidos Geofisicos Computacionales at Instituto Geofisico del Peru (grants 101-2014-FONDECYT, SPIRALES2012 IRD-IGP, Manglares IGP-IDRC, PP068 program).We also thank Mr. Luis Suarez Salas for the support of LAMAR instruments.